School principal leadership as a managerial mechanism in enhancing teacher performance - Bahdin Nur Tanjung (Indonesian Journal Education, 2025)
School leadership plays a critical role in shaping school effectiveness and teacher performance, particularly within the framework of educational management. This study aims to examine the role of school principal leadership as a managerial mechanism in enhancing teacher performance through a qualitative literature-based approach. Using a conceptual review design, this article analyzes and synthesizes scholarly literature published between 2021 and 2025 that addresses principal leadership, managerial functions, leadership styles, and teacher performance. The findings indicate that principal leadership operates as an integrated managerial mechanism encompassing planning, organizing, directing, and controlling school resources and instructional processes. Effective leadership is shown to influence teacher performance through organizational structures, instructional supervision, strategic decision-making, and trust-based relationships. Additionally, leadership styles such as instructional, transformational, and integrated leadership contribute significantly to teachers’ professional development and instructional effectiveness. This study contributes to educational management literature by clarifying the conceptual position of principal leadership as a managerial mechanism rather than a fragmented leadership construct. The findings emphasize the importance of managerial coherence in leadership practices to support sustainable improvement in teacher performance. Future research is encouraged to empirically examine this conceptual framework across diverse educational contexts.